Aspek-Aspek Hukum dalam Dunia Bisnis - Siti Fatimah; Elisa Widianti; Rista Emmy Azizah; Westri Maharani; Muhammad Fahmi (Publikasi Indonesia, 2022)
The purpose of this paper is to examine the legal aspects of business. In connection with any framework contained in business law, including knowing about legal definitions, business definitions, legal rules and business law, sources of business law, the scope of business law, business law theories, objects and subjects of business law, classification and business law groupings, as well as the functions and benefits of business law. Therefore, the results of this paper aim to explain all aspects of business law as a whole and it can be concluded that the aspects of business law are a science that has a very broad scope.